Performance Management in Public Organizations A Critical and Analytical View - Al-mutlaq, Naif (The Arab Journal of Administration, 2021)
This study aimed at introducing the performance management system and its philosophy to provide a critical and an analytical view of the most important points of strength and benefits. It also aimed at reviewing the most important challenges facing its applications to come up with general conclusions about this trend prevailing in organizations in general. The study focused on the applications of the performance management system in the public sector through summarizing the most important international experiences in the civil service. Such applications were analyzed from a critical perspective in order to determine the requirements for success in investing the performance management system in the public sector organizations. The study adopted the inferential theoretical approach that relies on the rational linking among the introductions, the results, and their explanations. The study also used observation and careful follow-up of the components of the concept of performance management through reviewing the related literature, scientific studies, reports and applications in government work. The study showed that there are several challenges facing the application of the job performance management approach in the public sector due to the different factors of cultural context for each organization, and the adoption of the successful models from some private sector organizations in some western countries. Therefore, the study came out with several recommendations that contribute to designing the road map to maximize the desired benefits from managing job performance in public organizations through wide-ranging reforms.